Amino Acid Analysis Protocols - Cooper, Catherine; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
Amino acid analysis is widely used in biotechnology, biomedical, and food analysis laboratories. Amino Acid Analysis Protocols constitutes a major collection of these indispensable analytical techniques, both classic and cutting-edge, of high utility for answering specific biological questions. Common methods include those based on HPLC or gas chromatography separation and analysis after precolumn derivatization. New techniques based on capillary electrophoresis separation, high-performance anion exchange chromatography, and mass spectrometry are also presented. Since results depend heavily on the quality of the sample, most contributors have devoted a section to sample preparation, particularly to the collection and storage of bodily fluids. A new method for desalting samples prior to hydrolysis is also provided. Each method is described in step-by-step detail to ensure successful experimental results, and contains helpful notes on pitfalls to avoid, and variations that enable the methods to be used with different systems. Up-to-date and highly practical, Amino Acid Analysis Protocols offers analytical and clinical chemists, as well as a broad range of biological and biomedical investigators, a rich compendium of laboratory tools for the productive analysis of both common and uncommon amino acids.
Amino Acid Analysis -- Amino Acid Analysis, Using Postcolumn Ninhydrin Detection, in a Biotechnology Laboratory -- Purification of Proteins Using UltraMacro Spin Columns or ProSorb Sample Preparation Cartridges for Amino Acid Analysis -- Amino Acid Analysis Using Precolumn Derivatization with 6-Aminoquinolyl-N-Hydroxysuccinimidyl Carbamate -- Amino Acid Analysis by High-Performance Liquid Chromatography after Derivatization with 1-Fluoro-2,4-Dinitrophenyl-5-L-Alanine Amide (Marfey's Reagent) -- The Analysis of Amino Acids Using Precolumn Derivatization, HPLC, and Electrochemical Detection -- Anion Exchange Chromatography and Integrated Amperometric Detection of Amino Acids -- Ion-Pair Chromatography for Identification of Picomolar-Order Protein on a PVDF Membrane -- Capillary Gas Chromatographic Analysis of Protein and Nonprotein Amino Acids in Biological Samples -- Measurement of Blood Plasma Amino Acids in Ultrafiltrates by High-Performance Liquid Chromatography with Automatic Precolumn O-Phthaldialdehyde Derivatization -- Determination of Amino Acids in Foods by Reversed-Phase High-Performance Liquid Chromatography with New Precolumn Derivatives, Butylthiocarbamyl, and Benzylthiocarbamyl Derivatives Compared to the Phenylthiocarbamyl Derivative and Ion Exchange Chromatography -- Amino Acid Measurement in Body Fluids Using PITC Derivatives -- Determination of Proteins, Phosphatidylethanolamine, and Phosphatidylserine in Lipid-Rich Materials by Analysis of Phenylthiocarbamyl Derivatives -- Analysis of O-Phosphoamino Acids in Biological Samples by Gas Chromatography with Flame Photometric Detection -- Determination of Sulfur Amino Acids, Glutathione, and Related Aminothiols in Biological Samples by Gas Chromatography with Flame Photometric Detection -- Capillary Electrophoretic Determination of 4-Hydroxyproline -- Total Plasma Homocysteine Analysis by HPLC with SBD-F Precolumn Derivatization -- Determination of Early Glycation Products by Mass Spectrometry and Quantification of Glycation Mediated Protein Crosslinks by the Incorporation of [14C]lysine into Proteins.
Keywords: Biochemistry; Biochemistry, general